Totally wacky facts about planets and stars - Berne, Emma Carlson (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2016)
"Presents at more than 100 facts about planets and stars in a unique layout that appeals to struggling and reluctant readers
A gift from book Africa
The World Around Us (Outer Space)
1 2 13 15
NEW_ZTN_GN
Keywords: Planets; Stars -- Miscellanea -- Juvenile literature